EVALUASI DAMPAK LIBERALISASI PERDAGANGAN TERHADAP INDIKATOR PEREKONOMIAN MAKRO INDONESIA : PENDEKATAN MODEL KESEIMBANGAN UMUM TERAPAN - Rini Setyastuti (KINERJA, 2003)
This paper tries to examine the impact of trade liberalization on the Indonesian macroeconomy. The analysis was accomplished by employing the INDORANI Computable General Equilibrium (CGE) model. INDORANI is a CGE model of the Indonesian economy developed by the Inter University Study Center on Economics of the Gadjah Mada University that has had relationship with the IMPACT PROJECT, Monash University, Australia since the early of 1997. The model is static in nature and focuses on the real-side of the economy and explicitly divides Indonesia into two regions, rural and urban.This study found that trade liberalization in Indonesia would have a positive effect on the Indonesian macroeconomy. We also found that the majority of the simulation long run effects would not be different from the short run effects. Both in the long run and the short run, the trade liberalization would have positive effects on economic growth. In the employment side, the increasing employment in the urban area would be more than in the rural area. From the stability side, the trade liberalization would decrease consumers price index and investment price index.From the redistribution side, the trade liberalization would increase income of capital and landowner, but decrease the income of labor. In the sector side, the trade liberalization would increase value added (except for manufactured product which is based on natural resources), export, and employment. Generally, domestic price in nine sectors examined would decrease, except in the mining sector. The importof rice, another plant, forestry, fishery and husbandry, mining and services sector would decrease, but for the other sectors.Keywords: trade liberalization, INDORANI Computable General Equilibrium, macroeconomy,sector